Administrative liability: features of legal relations involving correctional agencies - D. A. Grishin; A. S. Dugenets (Правоприменение, 2021)
The subject of the research is the modern administrative law and administrative procedural doctrine shaping the view of the contents and nature of the legal relationship of administrative liability involving correctional agencies.The purpose of the article is to confirm or disprove the hypothesis about significant features of legal relations of administrative liability arising, developing and terminating in the field of execution of criminal penalties.The methodology includes systematic analysis of legal academic literature, interpretation of Russian legislation on administrative offences.The main results. The static (universal for all law enforcement agencies) structure of the institution of administrative liability acquires its qualitative originality in the process of its practical implementation in the law enforcement activities of the relevant bodies and officials authorized by the state to bring to administrative responsibility through appropriate legal relations. The main part of the legal relations of administrative responsibility that develop in the activities of correctional institutions and pre-trial detention centers are of a security nature. These relations are primarily aimed not at implementing the main tasks of the legislation on administrative responsibility, but at achieving the basic goal of the functioning of penitentiary institutions, i.e. ensuring the public safety of objects of the Federal Penitentiary Service of Russia. Identification and proper procedural registration of the fact of an administrative offense will be the basis for the emergence of the corresponding protective legal relationship. The authors make proposals aimed at improvement of normative regulation and practice of application of administrative coercive measures, enforced by employees of the Federal Penitentiary Service of Russia. It is necessary to radically change the approach to the administrative and jurisdictional practice of correctional agencies by expanding the application of administrative responsibility to convicted persons and persons held in pre-trial detention centers.Conclusions. Administrative liability relations involving correctional agencies have specific features. The application of such liability is aimed at maintaining the normal legal regime and ensuring the public safety of the relevant penitentiary facility. Administrative responsibility should be applied by correctional agencies to citizens who are located on the territory of the penitentiary institution and pre-trial detention center, civil personnel of the penitentiary system and special agents. A doctrinal definition of the legal relationship of administrative liability involving correctional agencies is formulated by authors.